TANTANGAN PENGELOLAAN WILAYAH PESISIR DI KABUPATEN HALMAHERA SELATAN - Nusantara, Surya Dharma; Muhammad, Fuad; Maryono, Maryono; Rahman Halim, M. Arief (Jurnal Pengabdian Perikanan Indonesia, 2023)
Environmental damage due to anthropogenic activities is one of the important issues in dealing with the dangers of global warming. Sustainable development in coastal areas is very important considering the coast is a territorial boundary before land. This study aims to identify how the management, development and challenges of coastal areas in the future in South Halmahera Regency. This research is based on information from scientific literature and secondary data. The results of the study inform that integrated coastal management in South Halmahera Regency is currently not focused on coastal development strategies. Therefore, this coastal area requires integrated management to build reciprocal interactions between coastal communities, policies, and the environment to achieve sustainable development. This coastal area has a diversity of natural resources, minerals and tourism potential. It is necessary to take roles and initiatives in coastal environmental management. Judging from the results of trends in coastal management status, South Halmahera Regency has development opportunities that can reduce the impact of climate change and contribute to local economic development.